University students in COVID-19 lockdown: The role of adaptability and fluid reasoning in supporting their academic motivation and engagement. (February 2023) - Martin, Andrew J.; Ginns, Paul; Collie, Rebecca J.
Abstract: This study drew on Job Demands-Resources theory and data from 500 Australian university students to investigate the role of COVID-related lockdown, perceived adaptability, and fluid reasoning in students' self-efficacy—and the role of these factors in students' engagement and disengagement. Lockdown was associated with higher disengagement; perceived adaptability was associated with higher self-efficacy; and both perceived adaptability and fluid reasoning were significantly and positively associated with engagement. Self-efficacy significantly mediated the relationship between perceived adaptability and engagement and disengagement, while moderation tests revealed that fluid reasoning yielded a significant positive role for the self-efficacy of students in lockdown. These findings shed light on factors during COVID-19 that are implicated in students' academic development and provide direction for psycho-educational interventions. Highlights: Lockdown was associated with higher disengagement among university students. Perceived adaptability and fluid reasoning were associated with higher engagement. Self-efficacy mediated between adaptability and engagement and disengagement. Fluid reasoning had a positive role for the self-efficacy of students in lockdown.